Catalytic hydrotreatment of bio-oil from continuous HTL of Chlorella sorokiniana and Chlorella vulgaris microalgae for biofuel production. (June 2023) - da Costa Magalhães, Bruno; Matricon, Lucie; Ramirez Romero, Laura-Adriana; Checa, Ruben; Lorentz, Chantal; Chambonniere, Paul; Delrue, Florian; Roubaud, Anne; Afanasiev, Pavel; Laurenti, Dorothée; Geantet, Christophe
Graphical abstract: Image 1 Highlights: Continuous HTL of carbohydrate-rich and lipid-rich microalgae followed by HDT. Advanced characterization of HTL and HDT oils. The HTL bio-oil from rich-lipid microalgae was easier to upgrade. The HDT oils fell mainly in the diesel range. Biofuel yield was directly related to the biomass lipid content.